The TRiCky Business of Protein Folding in Health and Disease - Ghozlan, Heba; Cox, Amanda; Nierenberg, Daniel; King, Stephen; Khaled, Annette R. (Frontiers in Cell and Developmental Biology, 2022)
Maintenance of the cellular proteome or proteostasis is an essential process that when deregulated leads to diseases like neurological disorders and cancer. Central to proteostasis are the molecular chaperones that fold proteins into functional 3-dimensional (3D) shapes and prevent protein aggregation. Chaperonins, a family of chaperones found in all lineages of organisms, are efficient machines that fold proteins within central cavities. The eukaryotic Chaperonin Containing TCP1 (CCT), also known as Tailless complex polypeptide 1 (TCP-1) Ring Complex (TRiC), is a multi-subunit molecular complex that folds the obligate substrates, actin, and tubulin. But more than folding cytoskeletal proteins, CCT differs from most chaperones in its ability to fold proteins larger than its central folding chamber and in a sequential manner that enables it to tackle proteins with complex topologies or very large proteins and complexes. Unique features of CCT include an asymmetry of charges and ATP affinities across the eight subunits that form the hetero-oligomeric complex. Variable substrate binding capacities endow CCT with a plasticity that developed as the chaperonin evolved with eukaryotes and acquired functional capacity in the densely packed intracellular environment. Given the decades of discovery on the structure and function of CCT, much remains unknown such as the scope of its interactome. New findings on the role of CCT in disease, and potential for diagnostic and therapeutic uses, heighten the need to better understand the function of this essential molecular chaperone. Clues as to how CCT causes cancer or neurological disorders lie in the early studies of the chaperonin that form a foundational knowledgebase. In this review, we span the decades of CCT discoveries to provide critical context to the continued research on the diverse capacities in health and disease of this essential protein-folding complex.